Review of the Monograph “LegalTech in the Field of Entrepreneurship” - V. N. Shelmenkov; D. A. Gusev (Теоретическая и прикладная юриспруденция)
(ed. by I. V. Ershova, O. V. Sushkova, Moscow State Law University named after O. E. Kutaﬁn (MSUA). M.: Prospekt, 2022)At present, information and communication technologies are an integral part of our lives; without them it is now difﬁcult to imagine the existence and development of the human world. As a consequence, it should be noted that the rapid informatization of society has led to a phenomenon known as the automation of work processes. Modern jurisprudence also could not avoid this fate, and therefore every day the digitalization of legal activity attracts more and more interest from both legal scholars and those who are far from the legal profession. Performing such routine tasks as drafting contracts, document management, issuing licenses, with the help of artiﬁcial intelligence, the algorithms of which exclude the possibility of professional error, is no longer a fantasy, but a reality towards which humanity is successfully moving. Thus, Legal tech systems have become one of the ways to modernize jurisprudence.